Professional Sports and Empathy: Relationship Between Professional Futsal Players’ Tendency Toward Empathy and Fouls - Sezen-Balçikanli Gülfem; Sezen Mehmet (Physical Culture and Sport: Studies and Research, 2017)
The objective of this study is to determine the correlation between the professional futsal players’ (futsallers’) empathic tendency and the numbers of the cards they are shown and the fouls they commit. Empathy was assessed through a Turkish version of Interpersonal Reactivity Index-IRI. The original IRI takes as its starting point from the notion that empathy consists of a set of separate but related constructs, and seeks to provide measures of dispositional tendencies in several areas. The instrument contains four (seven-items) subscales, each tapping a separate facet of empathy. The items are scored on a 5-point Likert scale, with 0 (does not correspond at all to me) and 4 (corresponds exactly to me) serving as extreme points. Research group is composed of total 76 professional male futsal players who took part in Efes Pilsen Futsal League games with 7 teams from Ankara region. Age averages of all the participants were between the ages of 18 and 38 and their age average range was from 24 to 26. As a statistical method in the assessment of the research data; in order to examine the correlation between the general average, standart deviation, mean per team, standart deviation and professional futsal players’ empathy levels and the number of the cards they are shown (yellow/red) and their fouls, Spearman Rank Correlation was utilized. The results obtained demonstrate that there is a relationship between empathy and yellow/red cards and fouls. It is considered that the empathy practices to be developed for the sportspersons will develop perspective taking and interpersonal communication between them, enhance moral viewpoint and moral attitudes in sports in them, and reduce the aggressive behaviours and self-seeking actions.